2015
DOI: 10.1063/1.4919402
|View full text |Cite
|
Sign up to set email alerts
|

Automated cell viability assessment using a microfluidics based portable imaging flow analyzer

Abstract: In this work, we report a system-level integration of portable microscopy and microfluidics for the realization of optofluidic imaging flow analyzer with a throughput of 450 cells/s. With the use of a cellphone augmented with off-the-shelf optical components and custom designed microfluidics, we demonstrate a portable optofluidic imaging flow analyzer. A multiple microfluidic channel geometry was employed to demonstrate the enhancement of throughput in the context of low frame-rate imaging systems. Using the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 37 publications
(41 reference statements)
0
9
0
Order By: Relevance
“…Images can be analyzed using image processing programs . Jagannadh et al reported a portable version of the device for multichannel imaging (Figure f) …”
Section: Imaging Approaches For Dynamic Platformsmentioning
confidence: 99%
See 3 more Smart Citations
“…Images can be analyzed using image processing programs . Jagannadh et al reported a portable version of the device for multichannel imaging (Figure f) …”
Section: Imaging Approaches For Dynamic Platformsmentioning
confidence: 99%
“…f) Multiple field of view imaging of blood cell using a cellphone based imaging flow analyzer. Reproduced with permission . Copyright 2015, American Institute of Physics.…”
Section: Imaging Approaches For Dynamic Platformsmentioning
confidence: 99%
See 2 more Smart Citations
“…They also suggested that instead of a 3.2-MP (2048 × 1536 pixel) cellphone camera used in their experiments, a camera with 4-8 MP would capture the entire FOV with maximum resolution; cellphone cameras have since reached and surpassed this level of resolution. A similar system has been built for microfluidic imaging of red blood cells (Jagannadh et al, 2015). This cellphone microscopy system comprised a custom-built attachment for the cellphone, housing a microfluidic device, an eye-piece with 10× magnification and a 40× objective with 0.65 NA.…”
Section: Hardware Developmentsmentioning
confidence: 99%